2016
DOI: 10.4314/jasem.v20i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Determination of medical waste composition in hospitals of Sana'a city, Yemen

Abstract: The composition analysis of medical waste is generally considered to be the fundamental information for the most basic steps in the development of a plan for solid hospitals waste management. The objectives of this study were to determine the quantity, generation rate, and the physical composition of medical waste generated in hospitals of Sana'a city, Yemen. This cross-sectional, descriptive study was conducted on the composition of hospital wastes generated in four governmental hospitals in Sana'a City. Purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…The total number of samples that were positive for E. coli was 73 (36.5%), thirteen (13) of these were found in the hospital compound representing 17.8% of the total number of samples positive for E. coli. This percentage is higher than what was obtained in similar research by Alwabr et al (2016) who detected up to 12% prevalence of E. coli in dustbins and other hospital waste in Sana'a. It is also higher than the prevalence (10%) reported by Sharmin et al (2016).…”
Section: Discussioncontrasting
confidence: 71%
“…The total number of samples that were positive for E. coli was 73 (36.5%), thirteen (13) of these were found in the hospital compound representing 17.8% of the total number of samples positive for E. coli. This percentage is higher than what was obtained in similar research by Alwabr et al (2016) who detected up to 12% prevalence of E. coli in dustbins and other hospital waste in Sana'a. It is also higher than the prevalence (10%) reported by Sharmin et al (2016).…”
Section: Discussioncontrasting
confidence: 71%
“…Education also plays a significant role in the awareness level. 16 The current study revealed that educated patients had significantly higher awareness levels than low education levels or illiterate ones. The current study's findings are consistent with previous studies.…”
Section: Dovepressmentioning
confidence: 52%
“…The number of hospital beds in both public and private sectors in Sana'a city was 2765 beds. 16 Assuming a confidence level of 95%, a margin of error of 5%, and a response distribution of 50%, the minimum representative sample size was 338 based on Raosoft software (Raosoft. Inc., Seattle, USA).…”
Section: Study Population Sample Size and Sampling Methodsmentioning
confidence: 99%
“…The percentages of these components vary according to the country and type of hospital. Even in the same hospital, these components vary based on the nature of the departments/ward present in the hospital (Altin et al 2003 ; Alwabr et al 2016 ; Mohee 2005 ; Voudrias et al 2012 ).…”
Section: Importance Of Hospital Plastic Waste Managementmentioning
confidence: 99%
“…Alternatively, different expressions have been used for healthcare waste which includes hospital waste (S. Ali et al 2015 ; Altin et al 2003 ; Arshad et al 2011 ; Qadir et al 2002 ; Toheed et al 2005 ; Zeeshan et al 2009 ), medical waste (Alwabr et al 2010 ; Birpinar et al 2011 ; El-Ramady et al 2011 ; Komilis et al 2012 ; Mohee 2014 ; Patwary et al 2014 ), biomedical waste (Badni and Dharmashree 2016 ; Gautam et al 2016 ; Tiwari 2018 ), and infectious waste (Lee et al 2021 ), etc.…”
Section: Introductionmentioning
confidence: 99%